Pengaruh Panjang Tabung Udara Pompa Hidram Terhadap Debit Dan Ketinggian Air Irigasi - Kasimirus Kemara Herin; Dwi Purnomo; Arum Pratiwi; Lisa Navitasari (Jurnal Multidisiplin Dehasen (MUDE), 2026)
The utilization of reservoirs as a source of agricultural irrigation in Randuagung Village, Singosari District, Malang Regency, has not been optimal due to limitations in water distribution systems to agricultural land located at higher elevations. One of the appropriate technologies that can be applied to address this problem is a hydraulic ram pump, which operates without fuel or electrical energy. This study aimed to analyze the effect of air chamber length on the discharge and water lifting performance of a hydraulic ram pump. The research employed an experimental method using a Randomized Complete Block Design (RCBD) consisting of four air chamber length treatments, namely 30 cm (P1), 45 cm (P2), 60 cm (P3), and 75 cm (P4), with five replications for each treatment. The observed parameters included inlet discharge, outlet discharge, and water discharge at various delivery heights. Data were analyzed using Analysis of Variance (ANOVA) followed by the Least Significant Difference (LSD) test at a 95% confidence level. The results showed that air chamber length had no significant effect on inlet discharge, but significantly affected outlet discharge and the pump's ability to lift water. The treatment results obtained at an air tube length of 75 cm (P4) with an outlet discharge of 0.445 L/s. At the delivery height test, only P4 was able to deliver water up to a height of 9 meters with an average discharge of 0.0078 L/s. The findings indicate that increasing the air chamber length improves pressure stability, thereby enhancing the hydraulic ram pump's performance in lifting water.